ANALISIS EFEKTIVITAS PENYALURAN PINJAMAN PADA KSP. KOPDIT PINTU AIR CABANG KEWAPANTE - Odang, Maria Wildiyanti; Pati Sanga, Konstantinus; De Romario, Fransiscus (Universitas Nusa Nipa Maumere, 2025)
The purpose of this study is to analyze the effectiveness of loan distribution at KSP Kopdit Pintu Air Kewapante Branch. This study is a descriptive qualitative research using data collection techniques such as observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data display, and conclusion drawing. The results of this study show that the effectiveness of loan distribution at KSP Kopdit Pintu Air Kewapante Branch can be seen from several aspects, including loan granting procedures, risk management, and its impact on members. KSP Kopdit Pintu Air Kewapante Branch has implemented good procedures in loan distribution, but there needs to be improvement in risk management and supervision of loans granted. This is important to ensure the sustainability of the cooperative and the welfare of its members. Loan distribution at KSP Kopdit Pintu Air Kewapante Branch can be said to be quite effective if the distribution procedures are followed properly, credit risks are managed appropriately, and the impact on members is positive. It is important to continue to conduct regular evaluations and improvements to ensure that loan distribution continues to provide optimal benefits for members and the cooperative.